A benchmarking program to reduce red blood cell outdating: implementation, evaluation, and a conceptual framework. Issue 7 (16th March 2015) - Barty, Rebecca L.; Gagliardi, Kathleen; Owens, Wendy; Lauzon, Deborah; Scheuermann, Sheena; Liu, Yang; Wang, Grace; Pai, Menaka; Heddle, Nancy M.
<x xml:space="preserve">Abstract</x> BACKGROUND Benchmarking is a quality improvement tool that compares an organization's performance to that of its peers for selected indicators, to improve practice. STUDY DESIGN AND METHODS Processes to develop evidence‐based benchmarks for red blood cell (RBC) outdating in Ontario hospitals, based on RBC hospital disposition data from Canadian Blood Services, have been previously reported. These benchmarks were implemented in 160 hospitals provincewide with a multifaceted approach, which included hospital education, inventory management tools and resources, summaries of best practice recommendations, recognition of high‐performing sites, and audit tools on the Transfusion Ontario website (http://transfusionontario.org). In this study we describe the implementation process and the impact of the benchmarking program on RBC outdating. A conceptual framework for continuous quality improvement of a benchmarking program was also developed. RESULTS The RBC outdating rate for all hospitals trended downward continuously from April 2006 to February 2012, irrespective of hospitals' transfusion rates or their distance from the blood supplier. The highest annual outdating rate was 2.82%, at the beginning of the observation period. Each year brought further reductions, with a nadir outdating rate of 1.02% achieved in 2011. The key elements of the successful benchmarking strategy included dynamic targets, a comprehensive and evidence‐based implementation strategy, ongoing information sharing, and a robust data system to track information. CONCLUSION The Ontario benchmarking program for RBC outdating resulted in continuous and sustained quality improvement. Our conceptual iterative framework for benchmarking provides a guide for institutions implementing a benchmarking program.